Books in Brazil: a history of the publishing trade, de Lawrence Hallewell - Suaiden, Emir (Revista de Biblioteconomia de Brasília, 1983)
HALLEWELL, Lawrence. Books in Brazil: a history of the publishing trade. London: Scarecrow Press, 1982. 485p.